Analyzing and managing the disturbance in a mining port stockyard system - Ayu, Media Anugerah; Mantoro, Teddy (2010)
In a mining port stockyard, disturbance on incoming trains from the mining plants causes a major problem to the system. This paper presents an analysis of those disturbances in the stockyard system. A simulation study is performed in order to do the analysis. We investigated the effects of the occurrence of the disturbance on the system and proposed operational policies on how to respond effectively in order to reduce the effects to the system performance.